2013
DOI: 10.1158/0008-5472.can-13-0748
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tumorigenesis Stimulated by Raf Inhibitors Relies Upon Raf Functions That Are Dependent and Independent of ERK

Abstract: RAF inhibitors achieve unprecedented but mainly transient clinical responses in patients with melanoma whose tumors harbor an activating BRAF mutation. One notable side-effect of RAF inhibitors is the stimulation of cutaneous skin tumors, arising in about 30% of patients receiving these drugs, which are thought to develop as a result of inhibitor-induced activation of wild-type Raf in occult precursor skin lesions. This effect raises the possibility that less manageable tumors might also arise in other epithel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 29 publications
4
29
1
Order By: Relevance
“…The latter model confirmed that Ras activation, in the absence of other mutations or of inflammation, is enough to trigger Raf inhibitor‐driven tumorigenesis in both skin and gastric epithelia [92]. Thus, Ras + inhibitor‐induced Erk activation accelerates the growth of tumors originating from cells containing activated Ras [92,109,110]. Further common to both models is the concept that paradoxical activation of the pathway can only happen at low inhibitor concentration [92,107,108,110].…”
Section: Raf and Mek Inhibitors – Success Stories With Pitfallsmentioning
confidence: 58%
“…The latter model confirmed that Ras activation, in the absence of other mutations or of inflammation, is enough to trigger Raf inhibitor‐driven tumorigenesis in both skin and gastric epithelia [92]. Thus, Ras + inhibitor‐induced Erk activation accelerates the growth of tumors originating from cells containing activated Ras [92,109,110]. Further common to both models is the concept that paradoxical activation of the pathway can only happen at low inhibitor concentration [92,107,108,110].…”
Section: Raf and Mek Inhibitors – Success Stories With Pitfallsmentioning
confidence: 58%
“…While each group proposed a distinct mechanism to explain the effect, several themes overlapped (Figure 2B). RAF inhibitors promoted co-immunoprecipitation of RAF isoforms as well as association with RAS-GTP at cell membranes 25,76,78 , suggesting that the inhibitors promote CRAF homo- and heterodimerization and RAS-mediated activation. Moreover, site-directed mutagenesis of the putative dimer interface rendered CRAF resistant to paradoxical activation 77 .…”
Section: Development Of Atp Competitive Inhibitors Of Raf Kinase Actimentioning
confidence: 97%
“…Indeed, studies using the K5-SOS-F transgenic mouse model, in which mice are predisposed to epidermal tumors through keratinocyte-specific expression of a dominant active, farnesylated Son of Sevenless (SOS-F), have shown that RAF inhibitor treatment promotes RAF dimerization, activates ERK signaling, and suppresses Rho-Associated, Coiled-Coil Containing Protein Kinase 2 (Rokα) to potentiate Ras -driven epidermal tumorigenesis. 78 In addition to RAS mutations, oncoviruses have been implicated as initiating factors in a subset of cutaneous lesions. Papilloma virus and Merkel cell polyomavirus DNA were identified in BRAF inhibitor treated patient samples and vemurafenib promoted tumorigenesis in an HPV driven mouse model of SCC 91 .…”
Section: Clinical Use Of Raf Inhibitorsmentioning
confidence: 99%
“…Our results are in good agreement with data from the Rosen laboratory indicating that increased levels of wild-type Ras–GTP complexes can cooperate with Braf hypoactive mutants to trigger tumour development in epithelial cells 24 . Similarly, increasing the pool of Ras–GTP by a dominant active Sos is sufficient to induce MAPK hyperactivation and the formation of epithelial tumours in response to Raf inhibition 25 . Likewise, MAPK activation in primary keratinocytes carrying the Braf LSLD631A allele depended both on Craf and RTK signalling.…”
mentioning
confidence: 99%